Pencegahan Mastitis Subklinis Pada Sapi Perah dengan Menggunakan Bahan Herbal Sebagai Teat Dipping - Happy Aprillia Mahardika (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2022)
Subclinical mastitis is a disease caused by bacteria. The mastitis cases in dairy cows can be prevented by doing teat dipping. This study was conducted to compile sufficient information about the prevention of mastitis in dairy cows using herbal ingredients in the form of cherry leaves, betel leaves, moringa leaves, basil leaves, and "beluntas" leaves. The method used in this study was a Systemic Literature Review (SLR), literature study by collecting several previous research results to answer the role of herbs that can be used as ingredients to prevent mastitis in dairy cows. The data used is secondary data. The results of this literature study stated that cherry leaves, betel leaves, moringa leaves, basil leaves, and "beluntas" leaves can be used as natural ingredients in teat dipping to prevent mastitis in dairy cows. Natural ingredients in the form of cherry leaves, betel leaves, moringa leaves, basil leaves, and "beluntas" leaves phytochemically contain flavonoid compounds, tannins, saponins, and phenols which processed by the decoction method/boiled, juiced or extracted might be acts as antibacterials, further can be used as substitutes for teat dipping ingredients.